THE ROLE OF SOCIAL MEDIA ADVOCACY ON DRUG ABUSE AMONG THE YOUTHS IN OWO LOCAL GOVERNMENT - Adeyefa Christianah Ronke; Awofadeju Peter Olayinka (International Studies Journal)
This paper examined Social Media as Advocate for Sensitising the Youth in Owo Local Government on the Consequences of Drug Abuse. This paper employed Agenda setting theory. Moreover, this study adopted survey design method and Owo local government areawas selected as area of the study. The population of the study was 341,400and this consisted of the total population of the selected area. However the study considered 400 participants which make up the sampling size and this was derived from 341,400entire populations of the selected local government areas through Taro Yamane formula. The findings of this study revealed that, social media advocacy has played vital roles in sensitising the youth on the negative effects of drug abuse.  The study further revealed that, attitudinal change, public enlightening on the effects of drug abuse are necessary tools to reduce or eradicate drug abuse in the study area. Finally, the study recommends that, media should give much preference to issues relating to drug abuse as it will help to sensitise the general public on the negative effects of drug abuse. That, government at all level should consider social media as a functional medium of sensitising the general public on issue relating to drug abuse onpersonal health.